Necessity and relevance of qualitative research in pediatric dentistry. A literature review - Khlood Baghlaf (Saudi Dental Journal)
Objectives: This review aims to understand the essence and relevance of qualitative research in pediatric dentistry and summarizes the most important information needed for a pediatric dentist before conducting a qualitative study. Methods: An electronic search was conducted on studies published from December 2019 until December 2021 using PubMed, Scopus, and King Abdulaziz University Digital library. Several keywords were used to identify the studies for this review. Results: Thirty-three studies involving qualitative methods in pediatric dentistry have been conducted on parents and dentists. Qualitative studies in pediatric dentistry are used to explore the perceptions of mothers and their children and to understand their behavior in different areas related to pediatric dentistry. Barriers to conducting qualitative studies with children include credibility, the influence of others on children’s opinions, and differences that influence children’s behavior while conducting the study. Conclusion: Qualitative methods in pediatric dentistry have been conducted on parents and dentists; however, little is known about the credibility and trustworthiness of conducting qualitative research with children. Future studies are needed to investigate effective interview techniques with children and more research should be conducted to evaluate the credibility and trustfulness of using children as a source to collect data in qualitative research.